Delineation of a novel environmental phylogroup of the genus Acinetobacter encompassing Acinetobacter terrae sp. nov., Acinetobacter terrestris sp. nov. and three other tentative species - Nemec, Alexandr; Radolfová-Křížová, Lenka; Maixnerová, Martina; Nemec, Matěj; Španělová, Petra; Šafránková, Renata; Šedo, Ondrej; Lopes, Bruno S; Higgins, Paul G (Systematic and applied microbiology, 2021)
This study aimed to define the taxonomic position and structure of a novel, taxonomically unique group of 26 Acinetobacter strains, provisionally designated Taxon 24 (T24). The strains were recovered from soil and freshwater ecosystems (n = 21) or animals (n = 5) in Czechia, Scotland, Germany, the Netherlands and Turkey between 1993 and 2015. They were non-glucose-acidifying, nonhemolytic, nonproteolytic, growing at 32 °C and on acetate and ethanol as single carbon sources, but not on 4-hydroxybenzoate and mostly not at 37 °C. Their whole-genome sequences were 3.0-3.7 Mb in size, with GC contents of 39.8-41.3%. Based on core genome phylogenetic analysis, the 26 strains formed a distinct clade within the genus Acinetobacter, with strongly supported subclades termed T24A (n = 11), T24B (n = 8), T24C (n = 2), T24D (n = 3) and T24E (n = 2). The internal genomic ANIb values for these subclades were >94.8%, while the ANIb values between them were <92.5%. The results of MALDI-TOF MS-based analyses agreed with this classification. The five subclades differed from each other in the results of one to six carbon source assimilation tests. Given the genomic and phenotypic distinctness, internal coherence, numbers of available strains and geographically diverse origin of T24A and T24B, we propose the names Acinetobacter terrae sp. nov. and Acinetobacter terrestris sp. nov. for these two taxa, respectively. The type strains are ANC 4282v (= CCM 8986T = CCUG 73811T = CNCTC 8082T) and ANC 4471T (= CCM 8985T = CCUG 73812T = CNCTC 8093T), respectively. We conclude that these two species together with the other T24 strains represent a widely dispersed Acinetobacter clade primarily associated with terrestrial ecosystems.
Keywords: Animals; Core genome phylogeny; Germany; Netherlands; DNA bakterií; bakteriální geny; RNA, Ribosomal, 16S; DNA, Bacterial; hybridizace nukleových kyselin; Carbon source assimilation; Skotsko; Německo; Turkey; zastoupení bazí; půdní mikrobiologie; Fresh Water; Phylogeny; Scotland; Turecko; Nizozemsko; Acinetobacter; sladká voda; Czech Republic; Base Composition; Bacterial Typing Techniques; Soil Microbiology; MALDI-TOF MS; Sequence Analysis, DNA; Nucleic Acid Hybridization; Česká republika; techniky typizace bakterií; ekosystém; Ecosystem; Genes, Bacterial; zvířata; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S; Whole genome sequence